Dual-Band Filtering Differential Phase Shifter Using Cascaded Wideband Phase Shifter and Bandstop Network With Two Same Phase Shifts - Qiu, Lei-Lei; Zhu, Lei (IEEE microwave and wireless components letters, 2021)
This letter proposes a new design method of dual-band filtering differential phase shifter using cascaded wideband phase shifter and bandstop network. After cascading the bandstop network, the phase shift characteristic of the initial wideband filtering differential phase shifter remains unchanged, while its wide passband is divided into dual subpassbands. Compared with traditional dual-band-filter-based topology, the proposed cascaded one features the advantage of independently controlled phase and amplitude responses, and can achieve the same phase shifts in two passbands that conventional one cannot. For verification, a dual-band differential phase shifter with two same phase shifts of 90° is designed, fabricated, and measured. Simulated and measured results show good agreement.